Disease-free Survival and Local Recurrence After Laparoscopic-assisted Resection or Open Resection for Rectal Cancer: The Australasian Laparoscopic Cancer of the Rectum Randomized Clinical Trial. Issue 4 (April 2019) - Stevenson, Andrew R. L.; Solomon, Michael J.; Brown, Christopher S. B.; Lumley, John W.; Hewett, Peter; Clouston, Andrew D.; Gebski, Val J.; Wilson, Kate; Hague, Wendy; Simes, John
Abstract : Objective: The aim of the study was to determine the efficacy of laparoscopic rectal resection (Lap) versus open laparotomy and rectal resection (Open) for rectal cancer on locoregional recurrence (LRR) and disease-free survival (DFS) at 2 years. Summary background data: Although a Lap approach to colon cancer surgery may offer similar oncological outcomes to Open with potentially less morbidity, this remains to be clearly established for the treatment of rectal cancer. Methods: A randomized, multicenter noninferiority phase 3 trial of 475 patients with T1 to T3 rectal adenocarcinoma <15 cm from anal verge, given Lap or Open and followed for a minimum 2 years to assess LRR, DFS, and overall survival (OS). Results: Secondary endpoint analyses included 450 patients (95%) without metastases at baseline (mean age 64; 34% women) who received Lap (n = 225) or Open (n = 225). Median follow-up was 3.2 years (range: 0.1–5.4 yrs). LRR cumulative incidence at 2 years: Lap 5.4%; Open 3.1% [difference, 2.3%; 95% confidence interval (CI), −1.5% to 6.1%; hazard ratio (HR) 1.7; 95% CI, 0.74–3.9]. DFS at 2 years: Lap 80%; Open 82% (difference, 2.0%; 95% CI, −9.3% to 5.4%; HR for recurrence or death, 1.17; 95% CI, 0.81–1.68; P = 0.41). After adjustment for baseline factors HR = 1.07 (95% CI, 0.7–1.6). OS at 2 years: Lap 94%; Open 93% (difference 0.9%; 95% CI, −3.6% to 5.4%). Conclusions: Laparoscopic surgery for rectal cancer did not differ significantly from open surgery in effects on 2-year recurrence or DFS and OS. Confidence intervals included potentially clinically important differences favoring open resection, so that the combination of primary and secondary study endpoints may not support laparoscopic resection of rectal cancer as a routine standard of care and further follow-up is required. Abstract : Supplemental Digital Content is available in the text